2019
DOI: 10.1007/s11103-019-00938-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-epitope plant-made chimeric protein (LTBentero) targeting common enteric pathogens is immunogenic in mice

Abstract: Key message A plant-based multiepitopic protein (LTBentero) containing epitopes from ETEC, S. typhimurium, and V. parahaemolyticus was produced in plants cells and triggered systemic and intestinal humoral responses in immunized mice. Abstract Around 200 million people suffer gastroenteritis daily and more than 2 million people die annually in developing countries due to such pathologies. Vaccination is an alternative to control this global health issue, however new low-cost vaccines are needed to ensure prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…84,185,186 This procedure is not necessarily limited to a production of a single antigen, but several studies have focused on the preparation of so-called multivalent vaccines combining antigens of various pathogens or many epitopes of one pathogen. 49,[187][188][189] Importantly, plant production systems generate active recombinant antigens with adequate post-translational modifications.…”
Section: Benefits Of Plant-based Oral Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…84,185,186 This procedure is not necessarily limited to a production of a single antigen, but several studies have focused on the preparation of so-called multivalent vaccines combining antigens of various pathogens or many epitopes of one pathogen. 49,[187][188][189] Importantly, plant production systems generate active recombinant antigens with adequate post-translational modifications.…”
Section: Benefits Of Plant-based Oral Vaccinesmentioning
confidence: 99%
“…In addition to determining the localization of the recombinant antigen, its uptake can also be influenced by the incorporation of sequences encoding molecular adjuvants (CTBs, LTBs, flagellin, CPPs) and the creation of unique fusion proteins 84,185,186 . This procedure is not necessarily limited to a production of a single antigen, but several studies have focused on the preparation of so‐called multivalent vaccines combining antigens of various pathogens or many epitopes of one pathogen 49,187–189 …”
Section: Molecular Farming Of Fish Vaccinesmentioning
confidence: 99%
“…Given that plant systems have been successfully adopted for the production of multiepitope proteins, the generation of such vaccines against COVID-19 is considered highly viable [88][89][90]. Besides expressing chimeric proteins, multiple antigen expression can be achieved by transplastomic technologies (operon-like expression) or at the nuclear level using the picornaviral 2A sequence that allows releasing individual antigens from a single coding gene [91].…”
Section: Multiepitopic Vaccinesmentioning
confidence: 99%
“…Every day, 200 million people in the world experience health problems due to gastroenteritis. In developing countries, more than 2 million people die annually from such enteric diseases [23]. It has been reported that a multiepitopic protein from the antigens of enterotoxigenic E. coli, S. typhimurium and V. parahaemolyticus bacteria for use against these diseases is expressed in fresh leaf tissue as much as 5.29 μg g −1 in tobacco (Nicotiana tabacum) plants by A. tumefaciens-mediated transformation.…”
Section: Nuclear Transformationmentioning
confidence: 99%
“…It has been reported that a multiepitopic protein from the antigens of enterotoxigenic E. coli, S. typhimurium and V. parahaemolyticus bacteria for use against these diseases is expressed in fresh leaf tissue as much as 5.29 μg g −1 in tobacco (Nicotiana tabacum) plants by A. tumefaciens-mediated transformation. Plant-made LTBentero antigen was found to be immunogenic when administered orally or subcutaneously to BALB/c mice, this antigen was also able to induce specific IgG (systemic) and IgA (mucosal) responses against LTB, ST, and LptD epitopes [23]. Moreover, by regulating the quality processes of transgenic plant-based vaccines, it has been ensured that the quality differences in the production steps are minimized.…”
Section: Nuclear Transformationmentioning
confidence: 99%